Penanganan hiperplasia fibromatosis gingiva - Lenni Indriani Hatta (DiscoverSys Inc., 2009)
The treatment of oral cavity abnormality with diagnosis as hyperplasia fibromatousgingival, followed by immediate partial denture was purposed to provide esthetic ofhyperplasia protruded teeth. A case study was carried out to a 20 year-old female patientwith protrusive mobile anterior teeth and hyperplasia of the upper and lower jaw.Excision of gingival hyperplasia was made and the insertion of immediate partial dentureafter extraction of mobile and protrusive upper anterior teeth. Post-surgical and insertioncontrol were made after 24 hours, a week, and a month, and the gingival looks normally,esthetic and a better occlusion.